Teaching Biology in Primary Education - Tzovla, Eirini; Kedraka, Katerina (International Journal of Educational Technology and Learning, 2020)
This paper highlights the importance of teaching biological concepts in Primary Education and the need for enhancement in students of scientific literacy in general and biological literacy in particular. The students should be aware of the reality they experience in order to make decisions as active citizens and the teachers should use the best available methods and didactic approaches to enhance students’ scientific literacy and prepare them for their real life. In this regard, it is important to build curricula that utilize multiple learning resources and adopt student-centred methods and practices such as inquiry-based learning, collaborative learning and the use of digital educational content. These approaches boost the 21st-century skills through the active participation of students and improve the learning outcomes. Hence, teachers play a significant role, because they should know those methods and practices to utilize in transmitting the scientific knowledge to the students and teach effectively the biological concepts to them.